Social capital, perceived stress, and mental health of men who have sex with men in China: A cross-sectional study - Zhang, Xiaoyue; Zhou, Ying; Zhang, Kaili (Frontiers in Psychology, 2023)
Background：Mental health problems are prevalent among men who have sex with men (MSM). Social capital, perceived stress may affect the mental health of MSM. The purpose of this study was to understand the current status of mental health, social capital, and perceived stress among MSM and to explore which variables are influential factors of mental health. Methods: This study adopted a convenience sampling method and posted recruitment information through online social platforms (Blued, QQ and WeChat) from January 2022 to June 2022 to recruit participants. The questionnaire included a demographic questionnaire, Social Capital Questionnaire (SCQ), Perceived Stress Scale (PSS), and Self-Reporting Questionnaire 20 (SRQ-20). Descriptive analyses of demographic characteristics, social capital, perceived stress, and mental health were conducted using percentages, median, interquartile range, means, and standard deviations. One-way ANOVA and independent-samples t-test were used to test the relationship between demographic characteristics and mental health, and multiple linear regression was used to analyze which variables were influencing factors of mental health. SPSS 24.0 was used for data analysis, and significant differences were found at p < 0.05. Results: A total of 546 MSM participated in this study. Social capital score was 18.59 ± 2.6 2. PSS score was 26.91 ± 6.44, and SRQ-20 score was 7.5 (3, 11). Education level, relationship status, employed information, monthly income, sexual orientation, perceived stress, and three dimensions of social capital were included in the multiple linear regression based on the results of One-way ANOVA, t-test, and correlation analysis. Multiple linear regression analysis showed that relationship status, sexual orientation, perceived stress, social participation and social network had a significant effect on mental health. Conclusion: MSM have poorer mental health. Relationship status, sexual orientation, perceived stress, social networks, and social participation are important factors influencing mental health. The general public should be called upon to treat them with a more tolerant attitude, improve the social environment, and promote their identification with their sexual orientation, thereby reducing perceived stress and promoting the mental health of MSM. In addition,In addition, intervention from a social capital perspective may also be an important way to promote mental health.